Investigation of structural-mechanical properties of the recipe composition for special purpose fondants - Bloshchinska (Dudkina), Olena; Niemirich, Oleksandra; Havrysh, Andrey; Ishchenko, Tatiana; Tkachuk, Yuriy (My University, 2015)
У статті представлені результати експериментальних досліджень за такими параметрами, як пористість, адгезія, загальна деформація щільною частини фонданів. The article presents the results of experimental studies on parameters such as porosity, adhesion, general deformation of dense part of the fondants.
Keywords: гарячі солодкі страви; hot sweet dishes; поверхнево-активні речовини; surfactants; оптимізація; optimization; кафедра технології ресторанної і аюрведичної продукції; кафедра готельно-ресторанної справи